2020
DOI: 10.3390/inorganics8090049
|View full text |Cite
|
Sign up to set email alerts
|

The Ca2+-ATPase Inhibition Potential of Gold(I, III) Compounds

Abstract: The therapeutic applications of gold are well-known for many centuries. The most used gold compounds contain Au(I). Herein, we report, for the first time, the ability of four Au(I) and Au(III) complexes, namely dichloro (2-pyridinecarboxylate) Au(III) (abbreviated as 1), chlorotrimethylphosphine Au(I) (2), 1,3-bis(2,6-diisopropylphenyl) imidazole-2-ylidene Au(I) chloride (3), and chlorotriphenylphosphine Au(I) (4), to affect the sarcoplasmic reticulum (SR) Ca2+-ATPase activity. The tested gold compounds strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 42 publications
7
8
0
Order By: Relevance
“…This pump showed the highest affinity for the inhibitor compound 4, followed by compounds 2, 1, and 3. This inhibitory sequence was like that previously observed in the case of SERCA protein [18]. The IC 50 values obtained in our work with PMCA were similar to those reported for SERCA, except for compound 2, which presented a lower inhibitory potency regarding PMCA (IC 50 2.8 µM), in comparison with the value (IC 50 0.8 µM) obtained for SERCA [18].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This pump showed the highest affinity for the inhibitor compound 4, followed by compounds 2, 1, and 3. This inhibitory sequence was like that previously observed in the case of SERCA protein [18]. The IC 50 values obtained in our work with PMCA were similar to those reported for SERCA, except for compound 2, which presented a lower inhibitory potency regarding PMCA (IC 50 2.8 µM), in comparison with the value (IC 50 0.8 µM) obtained for SERCA [18].…”
Section: Discussionsupporting
confidence: 89%
“…This inhibitory sequence was like that previously observed in the case of SERCA protein [18]. The IC 50 values obtained in our work with PMCA were similar to those reported for SERCA, except for compound 2, which presented a lower inhibitory potency regarding PMCA (IC 50 2.8 µM), in comparison with the value (IC 50 0.8 µM) obtained for SERCA [18]. Therefore, these gold(I)-compounds and gold(III)-compounds showed high affinity for PMCA and SERCA.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The past decades have marked important advances in the traditional view of many roles that metals and their compounds play in biological systems. In fact, metals, inorganic compounds and/or metals-organic frameworks show a diversity of properties that allowed them to present several and distinct biological, environmental and health applications [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Recent insights into metals applications includes for instance, zinc nanoparticles as feed additives showing more efficiency than zinc salts, increasing growth not only in fish [1] but also in plants [2], besides preventing metal contaminants accumulation [2] and normalizing antioxidant biomarkers [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Polyoxotungstates (POTs), such as decatungstate (W 10 O 32 4− ), have shown, by photocatalytic activity, to decompose antibiotics namely sulfasalazine and sulfapyridine with different specificities and rates [5]. Besides green biotechnology applications, it was suggested that some POTs hamper melanoma cancer cells growth through inhibition of aquaporin-3 activity [6], whereas others POTs as well as gold compounds showed specific inhibitory activities for P-type ATPases [7,8].…”
Section: Introductionmentioning
confidence: 99%